The Role of Working Time Flexibility in Shaping Working Students’ Strategies Towards an Optimal Balance between Study and Work: A Phenomenological - Syaputra, Muhamad Ikhsan; Adrian, Muhamad (Proceeding of International Management Conference and Progressive Papers, 2025)
This study aims to analyze the influence of flexible working hours on the development of working students’ strategies for achieving an optimal balance between academic and work responsibilities. Using an interpretive phenomenological approach, this research explores the subjective experiences of working students in managing their dual roles. The findings reveal that flexible working hours serve as an essential factor that allows students to develop adaptive strategies such as effective time management, prioritization, and negotiation skills. These strategies help reduce stress, enhance self-efficacy, and improve overall satisfaction. The study emphasizes the need for universities and employers to implement flexible policies that support students’ well-being and academic achievement.